Logic programming and nonmonotonic reasoning : 13th International Conference, LPNMR 2015, Lexington, KY, USA, September 27-30, 2015. Proceedings /: 13th International Conference, LPNMR 2015, Lexington, KY, USA, September 27-30, 2015. Proceedings. (2015) - Unknown
No abstract available